Studi Komparasi Antara Mazhab Hanafi dan Mazhab Safi’i Tentang Wali Adhol - Ahmad Sibawai; Lalu Yoga Vandita (STIS DAFA MATARAM, 2022)
This study aims to (1) examine the perspectives of the Hanafi and Syafi’i schools of thought (mazhab) regarding the concept of wali adhol in marriage contracts, and (2) evaluate the relevance of these perspectives in the context of marriage in Indonesia. The research employs a qualitative approach with library research as its primary method. Data analysis is conducted using a comparative method, which juxtaposes the two mazhab's views to draw conclusions. The findings reveal that the Hanafi school does not require the presence of a guardian (wali) for a legally competent and mature woman in a marriage contract, except for minors and individuals with mental incapacities. If a guardian refuses a competent woman’s request to marry a suitable partner, the guardian is deemed ineligible to refuse (adhol). Conversely, the Syafi’i school mandates the presence of a guardian for all marriage contracts, whether for a mature woman or a widow. In the Indonesian context, the Hanafi school’s perspective is considered more relevant due to its flexible approach, which takes local customs into account and grants greater autonomy to brides in deciding their marriage arrangements. This study contributes by providing a comparative perspective on the role of guardians in Islamic marriage law, serving as a reference for the development of family law in Indonesia, particularly in addressing cases involving wali adhol.